A community-based study of asthenopia in computer operators. - Bhanderi DJ; Choudhary S; Doshi VG; Bhanderi, Dinesh J; Choudhary, Sushilkumar; Doshi, Vikas G (Indian Journal of Ophthalmology, 2008)
Context: There is growing body of evidence that use of computers can adversely affect the visual health. Considering the rising number of computer users in India, computer-related asthenopia might take an epidemic form. In view of that, this study was undertaken to find out the magnitude of asthenopia in computer operators and its relationship with various personal and workplace factors.Aims: To study the prevalence of asthenopia among computer operators and its association with various epidemiological factors.Settings and Design: Community-based cross-sectional study of 419 subjects who work on computer for varying period of time.Materials and Methods: Four hundred forty computer operators working in different institutes were selected randomly. Twenty-one did not participate in the study, making the nonresponse rate 4.8%. Rest of the subjects (n = 419) were asked to fill a pre-tested questionnaire, after obtaining their verbal consent. Other relevant information was obtained by personal interview and inspection of workstation.Statistical Analysis Used: Simple proportions and Chi-square test.Results: Among the 419 subjects studied, 194 (46.3%) suffered from asthenopia during or after work on computer. Marginally higher proportion of asthenopia was noted in females compared to males. Occurrence of asthenopia was significantly associated with age of starting use of computer, presence of refractive error, viewing distance, level of top of the computer screen with respect to eyes, use of antiglare screen and adjustment of contrast and brightness of monitor screen.Conclusions: Prevalence of asthenopia was noted to be quite high among computer operators, particularly in those who started its use at an early age. Individual as well as work-related factors were found to be predictive of asthenopia.